Pemberdayaan Kelompok Usaha Berbasis Minyak Atsiri Di Desa Kesamben, Blitar - Vivi Nurhadianty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
The business group located in Desa Kesamben, Blitar has business in the diversification of essential oil products. This business group is experiencing difficulties in expanding its business due to lack of innovation in producing volatile essential oil and inbuilt economic management. This activity helps the business group in developing the innovation of essential oil products through the creation of blending aroma. The training provided aims to make this business group able to mix the aroma of essential oil so that the product produced can be accepted by the consumers and have a distinctly different aroma. This essential oil-based wind oil product can be the product of